2007
DOI: 10.15578/iaj.2.2.2007.75-88
|View full text |Cite
|
Sign up to set email alerts
|

FATTY ACID PROFILES OF CYCLOPOID COPEPOD NAUPLII Apocyclops panamensis AND THE EFFECTS OF SALINITY CHANGE

Abstract: <p>Lipid and fatty acid profiles were described for copepod nauplii Apocy clops panamensis from fertilized brackish water ponds, and after being acclimated to fullsea water salinity. Mean total lipid content of copepod nauplii collected from ponds fertilized with inorganic fertilizer combined either with alfalfa meal, rice bran, wheat bran, and a combination of these fertilizers ranged from 5.66 ± 0.15 to 7.76% ± 0.27%. Non-polar (neutral) lipid fraction of pond copepod nauplii was a significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Sumiarsa (2003) reported that lipid contents of cyclopoid copepod nauplii Apocyclops panamensis cultured in fertilized earthen ponds were between 5.7%- Co pepo d nauplii fed w it hFat t y ac id s 7.8% with DHA/EPA ratios of 1.6-2.4 while the lipid contents of nauplii enriched with several commercial enriching agents were between 5.7-10.8 with DHA/EPA ratios of 1.0-3.3.…”
Section: Effect Of Microalgae On Growth (Gede Suwarthama Sumiarsa)mentioning
confidence: 99%
“…Sumiarsa (2003) reported that lipid contents of cyclopoid copepod nauplii Apocyclops panamensis cultured in fertilized earthen ponds were between 5.7%- Co pepo d nauplii fed w it hFat t y ac id s 7.8% with DHA/EPA ratios of 1.6-2.4 while the lipid contents of nauplii enriched with several commercial enriching agents were between 5.7-10.8 with DHA/EPA ratios of 1.0-3.3.…”
Section: Effect Of Microalgae On Growth (Gede Suwarthama Sumiarsa)mentioning
confidence: 99%